The effect of refolding conditions on the protein solubility recovered from inclusion bodies - Leong, C. Y.; Chua, Gek Kee; Rozaimi, Abu Samah; Chew, Few Ne (Penerbit UTEM, 2019)
Recombinant proteins are expressed as inclusion bodies in bacterial enriched native-like secondary structure and thus give a great potential in biotechnological utilities. However, the quality of soluble proteins recovered from inclusion bodies is questionable because the refolded protein with wrong conformation will assemble to form aggregates. In this study, enhanced green fluorescent protein-inclusion bodies was used as the model protein to investigate the effects of protein concentration and purity on protein refolding. Three different types of solubized enhanced green fluorescent protein-inclusion bodies were refolded which were solubized inclusion bodies with cell debris, solubized inclusion bodies with detergent washing, and purified solubized inclusion bodies using preparative native urea-polyacrylamide gel electrophoresis. For the first and second conditions, the solubized enhanced green fluorescent protein-inclusion bodies were refolded at a high protein concentration and low protein purity environment. Polyacrylamide gel images show the refolded protein changed in conformation and increased in size when the solubized inclusion bodies underwent various refolding periods. Meanwhile, the refolded protein under the third refolding condition has a correct protein conformation and achieved the highest refolding yield. Studying the effects of refolding conditions using different types of solubized inclusion bodies may provide researchers with possible approaches to avoid soluble aggregates formation.